Spending Smart: The Role of Government Expenditure in Boosting Provincial Economic Performance in Indonesia - Fauzan, Muhammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the impact of local government spending (expenditure) for the agricultural and industrial sectors on the economic performance of provinces in Indonesia. This study uses secondary data from the World Bank, the Central Bureau of Statistics, and the Ministry of Finance. The research data is in the form of panel data for 8 years for 33 provinces in Indonesia. The data was analyzed using an econometric model with a simultaneous equation system consisting of 9 structural and four identity equations. The results of the study revealed that the previous year's budget largely determined local government spending for the agricultural and industrial sectors and was not based on the development needs of the sector. In order to achieve the goals of economic development, namely increasing economic growth and reducing income inequality, local governments should implement policies by increasing the proportion of the budget for the agricultural sector. Increasing local government spending for the agricultural sector can also attract non-agricultural investment through increasing GRDP in the agricultural sector and reducing poverty.